2021
DOI: 10.17060/ijodaep.2021.n1.v2.2115
|View full text |Cite
|
Sign up to set email alerts
|

Implicancias socioeducativas de la generatividad en educadores rurales chilenos

Abstract: La generatividad se transforma en una dimensión educativa prometedora entre quienes ejercen la profesionalidad docente rural en contexto escolares chilenos. Su desarrollo estaría dado por el conjunto de comportamientos, prácticas y estrategias que orientan el quehacer profesional del educador rural, manifestándose en los saberes, experiencias y dinámicas relacionales que establecen con el alumnado y sus comunidades de origen, favoreciendo el reconocimiento histórico-cultural de las tradiciones y característica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(16 reference statements)
0
3
0
1
Order By: Relevance
“…In this regard, it is possible to point out that the study of the generative potential observed in Chilean rural teachers is an emerging topic in the local context, and there is still an exploratory approach to the topic in the Chilean context [82]. However, the emerging categories show that rural teachers expressed a generative expression that is coherent and consistent with their work role [20], fostering the deployment of autonomy, responsibility and active involvement in their teaching role [83], taking advantage of the opportunities for pedagogical development provided by the rural context, as well as the historical-cultural valuation of the customs and knowledge present in the territory [71,73,75,83,84].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, it is possible to point out that the study of the generative potential observed in Chilean rural teachers is an emerging topic in the local context, and there is still an exploratory approach to the topic in the Chilean context [82]. However, the emerging categories show that rural teachers expressed a generative expression that is coherent and consistent with their work role [20], fostering the deployment of autonomy, responsibility and active involvement in their teaching role [83], taking advantage of the opportunities for pedagogical development provided by the rural context, as well as the historical-cultural valuation of the customs and knowledge present in the territory [71,73,75,83,84].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, it would be interesting to delve into what types of potentially generative activities, tasks and/or experiences are those that would have a greater predictive weight for the development of generativity in those individuals who engage in caring tasks, beyond procreativity (family care through parenthood and grandparenthood), social participation (through civic or political engagement, in addition to other forms of non-family care) and creativity [71,[82][83][84].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erikson (1970), se refiere al concepto de generatividad como el reto al que la persona enfrenta en la mediana edad. Particularmente, emerge un interés por guiar y asegurar el bienestar de las siguientes generaciones y, en último término, por dejar un legado que trascienda en el tiempo (Sandoval-Obando, 2021a;2021b). De igual manera, Sandoval-Obando y Zacarés (2020) enfatizan que la generatividad se puede expresar a partir de actividades como la crianza de los hijos, el cuiado de los nietos (abuelidad), el Brazilian Journal of Development, Curitiba, v.7, n.11, p. 105006-105029 nov. 2021 cuidado de personas dependientes o en situación de discapacidadd, la formación de los jóvenes (mentorazgo), la producción de bienes y servicios o el compromiso social y la participación cívica y política, etc.…”
Section: Algunos Indicadores Respecto Al Envejecimiento En Chileunclassified